2003
DOI: 10.1002/adsc.200390037
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis with N‐Heterocyclic Carbenes. Application to the Copper‐Catalyzed Conjugate Addition

Abstract: Chiral N‐heterocyclic carbenes are good ligands for the copper‐catalyzed conjugate addition of dialkylzinc reagents to various Michael acceptors. With as little as 4% of chiral ligand, the enantioselectivity may reach 93% on cycloheptenone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(53 citation statements)
references
References 36 publications
0
52
0
1
Order By: Relevance
“…Other research groups have reported that a cis isomer yields a product with significant loss of enantioselectivity because of steric or other energetically competitive interactions between the catalyst and the substrate. [10] Two exceptions to this observation were reported by Okamoto and co-workers [11] in the addition of Grignard reagents to various allylic silylated ethers using chiral diaminocarbene catalysts, [12] and by Gennari and co-workers in the desymmetrization of meso cyclic allylic bisphosphates. [13] Table 1 summarizes the comparative results for the asymmetric addition of cyclohexylmagnesium chloride to the trans and cis isomers of 1,4-dichloro-2-butene (1 and 2, respectively), promoted by a small range of biphenol- [14] and binaphtol-based [6b, 15] phosphoramidite ligands (Scheme 1).…”
mentioning
confidence: 84%
“…Other research groups have reported that a cis isomer yields a product with significant loss of enantioselectivity because of steric or other energetically competitive interactions between the catalyst and the substrate. [10] Two exceptions to this observation were reported by Okamoto and co-workers [11] in the addition of Grignard reagents to various allylic silylated ethers using chiral diaminocarbene catalysts, [12] and by Gennari and co-workers in the desymmetrization of meso cyclic allylic bisphosphates. [13] Table 1 summarizes the comparative results for the asymmetric addition of cyclohexylmagnesium chloride to the trans and cis isomers of 1,4-dichloro-2-butene (1 and 2, respectively), promoted by a small range of biphenol- [14] and binaphtol-based [6b, 15] phosphoramidite ligands (Scheme 1).…”
mentioning
confidence: 84%
“…30) [65]. In this study, several Ag/carbene complexes (20)(21)(22)(23)(24) were tested and found to produce significantly higher ee values than those in previous studies.…”
Section: Equation 29mentioning
confidence: 62%
“…Reaction of the imidazolium chlorides 7 and 8 with Ag 2 O, following the procedure reported by Alexakis et al, 45 cleanly afforded the Ag(I) complexes 1,3-bis-(1(S)-1-phenyl-ethyl)-imidazolin-2-ylidene silver chloride 9 and 1,3-bis-(1(S)-1-naphthyl-ethyl)-imidazolin-2-ylidene silver chloride 10 respectively. Finally, transmetallation from Ag(I)-NHC complexes to a gold(I) centre was effected by reaction of these complexes with ClAu(THT) 47 (where THT = tetrahydrothiophene), 48 and afforded analytically pure samples of 11 and 12 after a single recrystallisation from CH 2 Cl 2 /hexane.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 93%
“…The chiral, cyclometallated, complex 4, and 5 were prepared according to Scheme 1 starting from readily available 43 The chiral imidazolium salts 6, 7 and 8 which were required for the preparation of the gold NHC complexes 11 and 12 were synthesised by the 'one-pot' procedures reported by Alexakis et al 45 and Hermann and co-workers (Scheme 2). 46 Hence, reaction of either (S)-(-)-α-methylbenzylamine or (S)-(-)-1-(1-naphthyl)ethylamine with glyoxal and paraformaldehyde in the presence of either HCl or HBF 4 at 40 °C in toluene overnight afforded the desired salts.…”
Section: Synthesis Of Chiral Gold Complexesmentioning
confidence: 99%